Case Report: Successful weaning after 113 days of VV-ECMO in a pediatric patient with severe ARDS following Stevens–Johnson syndrome - Beil, Korbinian; Hermann, Matthias; Haas, Nikolaus; Dalla-Pozza, Robert; Michel, Sebastian; Jakob, Andre; Fischer, Marcus; Pattathu, Joseph (Frontiers in Pediatrics, 2025)
Veno-venous extracorporeal membrane oxygenation (VV-ECMO) is an established rescue therapy for severe pediatric acute respiratory distress syndrome (ARDS), but prolonged support is rarely reported. We describe the case of a previously healthy 6-year-old boy who developed Stevens–Johnson syndrome (SJS), complicated by progressive respiratory failure and severe ARDS. Despite maximal ventilation, oxygenation remained insufficient, and VV-ECMO was initiated on day 11 of illness. Cannulation was performed via jugular and femoral access, followed by lung-protective ventilation, repeated surfactant administration, corticosteroid therapy according to the Meduri protocol, and angiotensin-converting enzyme inhibitor therapy. ECMO support was complicated by pulmonary fibrosis, cholestatic liver dysfunction with secondary hemochromatosis, and prolonged sedation-associated delirium with subsequent critical illness polyneuropathy. The first attempt to discontinue ECMO after 90 days failed due to presumed pulmonary embolism, requiring recannulation. Ultimately, successful weaning was achieved after 113 days of VV-ECMO. The patient was transferred to a specialized pulmonary and neurological rehabilitation center and discharged home after 6 months, still dependent on a tracheostomy cannula. At the 18-month follow-up, he required only nocturnal mechanical ventilation through the tracheostomy, was attending school, and led an otherwise normal life. A trial removal of the cannula with closure of the stoma is scheduled for spring 2026. This case illustrates that prolonged VV-ECMO can allow lung recovery in pediatric patients with ARDS secondary to SJS, despite complications. Careful multidisciplinary management and preserved neurological function were key factors supporting long-term survival.